2016
DOI: 10.1097/md.0000000000002206
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Therapy Modulates Cortical Perfusion in Parkinson Disease With and Without Dementia According to Arterial Spin Labeled Perfusion Magnetic Resonance Imaging

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Gray matter atrophy and cortical thinning in the thalamus have been reported in PD‐MCI (Chen et al, ; Danti et al, ). Previous ASL studies found decreased thalamic CBF in PD patients including PD‐D with relatively advanced disease (Lin et al, ; Melzer et al, ). The present study shows that a thalamic hemodynamic abnormality also occurs in PD‐MCI with early stage disease.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Gray matter atrophy and cortical thinning in the thalamus have been reported in PD‐MCI (Chen et al, ; Danti et al, ). Previous ASL studies found decreased thalamic CBF in PD patients including PD‐D with relatively advanced disease (Lin et al, ; Melzer et al, ). The present study shows that a thalamic hemodynamic abnormality also occurs in PD‐MCI with early stage disease.…”
Section: Discussionmentioning
confidence: 87%
“…Arterial spin labeling (ASL) is a magnetic resonance imaging (MRI) method for quantifying cerebral blood flow (CBF) and arterial transit time (ATT) by using magnetically labeled arterial blood water as an endogenous tracer. Because it is entirely noninvasive, and needs no radioactive tracer or other contrast agent (Detre, Leigh, Williams, & Koretsky, ), ASL has been increasingly used to investigate perfusion in healthy controls (HCs) and several neurological and psychiatric disorders (Hales, Kawadler, Aylett, Kirkham, & Clark, ; Lin et al, ; Lui et al, ), including PD (Al‐Bachari et al, ; Al‐Bachari, Vidyasagar, Emsley, & Parkes, ; Fernandez‐Seara et al, ; Lin et al, ; Melzer et al, ; Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive function is associated with cortical atrophy in PD patients, such that PD patients with cognitive impairments may show more extensive cortical atrophy and decreased cortical perfusion compared with PD patients without cognitive impairments (Ibarretxe-Bilbao et al, 2009; Chen et al, 2016; Lin et al, 2016) Relatedly, in PD patients with dementia, a previous study reported extensive frontal and subcortical atrophy compared with PD patients with no cognitive impairment (Borroni et al, 2015). The results of this study, meanwhile, show extensive WM changes even in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…All the image processing procedure, including tissue segmentation, study specific template construction, spatial normalization, and CBF partial volume effect (PVE) correction were conducted according to previous study (13) and was summarized in Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%